Nanotribological characteristics of laser surface melted Stellite 12+Mo hardfacing. Issue 2 (26th November 2018) - Dilawary, Shaikh Asad Ali; Motallebzadeh, Amir; Afzal, Muhammad; Atar, Erdem; Cimenoglu, Huseyin
Abstract : Purpose: The purpose of the study is to examine the sliding wear performance of plasma transfer arc (PTA) deposited and laser surface melted (LSM) Mo modified Stellite 12 hardfacings under high contact stresses (i.e. >20 GPa). Design/methodology/approach: For this purpose, after structural characterization, sliding wear tests have been conducted using sphero-conical diamond indenter as the counterface with different normal loads. The wear tracks formed on the hardfacings were examined by atomic force microscopy and scanning electron microscopy. Findings: Both hardfacings showed severe wear (at high contact stress levels ranging from 24 to 41 GPa), which progressed by plastic deformation, although the wear resistance of LSMed hardfacings was better than the PTA hardfacings by a factor of two due to its near surface microstructure characterized as carbide-rich zone. Originality/value: Sliding wear characterization of a promising 10 Wt.% Mo modified version of commercial Stellite 12 hardfacings (as reported previously by authors) was done in as PTA and LSMed states using nanomechanical test system. To the best of authors' knowledge, no report is available in the open literature on such hardfacings under these testing conditions.